A BURNING QUESTION: DOES ARSON INCREASE WHEN LOCAL HOUSE PRICES DECLINE?. Issue 1 (21st May 2015) - Eriksen, Michael D.; Carson, James M.
Abstract : We construct panel data on house prices and the determined cause of 4.8 million individual fires in the United States between 1986 and 2010 to test whether decreases in local housing market prices coincided with increases in arson. Since some insured homeowners may attempt to disguise the actual cause of fire as accidental, we also examine how decreases in local house prices are associated with changes in the total number of fires and the probability of determined causes of accidental fires. For the sample period, our results suggest that declines in local house prices coincided with increases in arson, the total number of fires, and the probability that fires were determined to occur due to arson and misuse. We provide further support for the existence of such an effect with empirical evidence that the relation between declines in house prices and arson is stronger in states that allow mortgage lender recourse.